2013
DOI: 10.1111/bjh.12579
|View full text |Cite
|
Sign up to set email alerts
|

Second autologous transplant as salvage therapy in multiple myeloma

Abstract: SummaryHigh-dose chemotherapy followed by autologous haematopoetic stem cell transplantation (ASCT) is a standard frontline therapy for multiple myeloma (MM). Unfortunately, there are no randomized clinical studies examining the role of a second ASCT in patients who relapse after the initial autotransplant. Analysing all available retrospective studies, it seems that salvage ASCT can safely be performed in most patients with an overall treatment-related mortality rate <5%. Approximately 65% of patients will ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 52 publications
(95 reference statements)
2
28
0
Order By: Relevance
“…If the response duration after the initial transplant was less than 1 year, stem cell transplantation could not be recommended as an effective intervention. 87 Currently at Mayo, we routinely collect sufficient stem cells for 2 transplants but do not perform tandem transplantations; we keep an aliquot cryopreserved for a second transplant at relapse.…”
Section: Plerixafor Dosingmentioning
confidence: 99%
“…If the response duration after the initial transplant was less than 1 year, stem cell transplantation could not be recommended as an effective intervention. 87 Currently at Mayo, we routinely collect sufficient stem cells for 2 transplants but do not perform tandem transplantations; we keep an aliquot cryopreserved for a second transplant at relapse.…”
Section: Plerixafor Dosingmentioning
confidence: 99%
“…Previous retrospective studies have indicated that a second ASCT is beneficial at relapse, at least if relapse occurs later than 18 months from initial treatment. 11 However, the development of novel drugs, for example, PI and IMiDs 1,[12][13][14][15] have raised the question if a second ASCT could be replaced by these drugs in second line. [16][17][18] A recent prospective study has shown that HDT followed by ASCT is superior to a cyclophosphamide-based regimen but data are lacking for comparing the novel drugs to ASCT.…”
Section: Introductionmentioning
confidence: 99%
“…The predictor historically associated with worse TTP after salvage auto-SCT is the response duration after the first auto-SCT. [25] Alvares et al confirmed this finding in 83 patients treated with a salvage second auto-SCT. Twenty patients had relapsed within 18 months from the first auto-SCT.…”
Section: Treatment Of Post Auto-sct Relapsementioning
confidence: 78%